2016
DOI: 10.1039/c6cp00663a
|View full text |Cite
|
Sign up to set email alerts
|

Exploring ion induced folding of a single-stranded DNA oligomer from molecular simulation studies

Abstract: One crucial issue in DNA hydration is the effect of salts on its conformational features. This has relevance in biology as cations present in the cellular environment shield the negative charges on the DNA backbone, thereby reducing the repulsive force between them. By screening the negative charges along the backbone, cations stabilize the folded structure of DNA. To study the effect of the added salt on single-stranded DNA (ss-DNA) conformations, we have performed room temperature molecular dynamics simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 84 publications
3
21
0
Order By: Relevance
“…Therefore, we utilized the ED-10 structure to model anti-dsDNA-antibody complexes. Recently, it was reported that aromatic interactions mediate the 5′-base specificity of the ssDNA-binding antibody ED-10 31 . In our model, ED-10 binds to base pairs within double helix, leading to partially unwound dsDNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we utilized the ED-10 structure to model anti-dsDNA-antibody complexes. Recently, it was reported that aromatic interactions mediate the 5′-base specificity of the ssDNA-binding antibody ED-10 31 . In our model, ED-10 binds to base pairs within double helix, leading to partially unwound dsDNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple healthy subjects had elevated titers of a-ssDNA, but not of a-dsDNA. This could be caused by coiling of the ss antigen into 3D shapes that may interact non-specifically 31 . Previously it was suggested that elevated a-ssDNA titers is a distinctive feature of drug-induced SLE (DISLE) 32 .…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 2A, MD simulations on a single strand of the Dickerson-Drew dodecamer showed the molecule undergoing large conformational changes, transforming from an ordered base-stacked form to a globular coil structure, in the nanosecond time scale [43]. Counterions stabilize the globular conformation by neutralizing intra-strand repulsion between phosphate backbones thereby favoring ssDNA folding [44]. The conformational transition is mediated by formation of basestacking interactions between non-consecutive bases (i with i + 2 or i + 3).…”
Section: Dynamical Conformers Of Homopolymeric Ssdnamentioning
confidence: 99%
“…Salt ions can regulate the effective interactions among polyelectrolytes such as colloids [1][2][3][4][5][6][7], nucleic acids [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], and proteins [23][24][25][26][27][28][29], and consequently impact diverse physical phenomena including the structural assembly of polyelectrolytes [30], the stability of colloids [31,32], and the collapse of nucleic acids [33][34][35]. Generally, a polyelectrolyte solution is often modeled through the Poisson-Boltzmann (PB) equation since the equation has a simple form and is rather successful in predicting the properties of polyelectrolytes in aqueous and monovalent salt solutions [36,37].…”
Section: Introductionmentioning
confidence: 99%